1996
DOI: 10.1210/jcem.81.9.8784083
|View full text |Cite
|
Sign up to set email alerts
|

The role of luteinizing hormone-beta gene polymorphism in the onset and progression of puberty in healthy boys.

Abstract: An immunologically anomalous LH with two point mutations in its beta-subunit gene (Trp8Arg and Ile15Thr) has recently been described. This polymorphism is common in Finland; 28% of the population are homo- or heterozygous for the variant allele. To assess the effect of the LH variant on LH action, we correlated its presence in a group of 49 healthy boys with the onset and progression of puberty. This group was followed-up longitudinally from a mean age of 11.7 +/- 0.1 yr for 3 yr at 3-month intervals. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…Tapanainen, K. Pettersson, & I. Huhtaniemi, unpublished observation). We have also found that boys with v-LH have slower overall progression, gain of height and gain of testis weight at puberty (Raivio et al, 1996). These findings suggest that the bioactivity of v-LH may be lower than that of the wt hormone.…”
Section: A Common Genetic Variant (V) Of Lhsupporting
confidence: 51%
“…Tapanainen, K. Pettersson, & I. Huhtaniemi, unpublished observation). We have also found that boys with v-LH have slower overall progression, gain of height and gain of testis weight at puberty (Raivio et al, 1996). These findings suggest that the bioactivity of v-LH may be lower than that of the wt hormone.…”
Section: A Common Genetic Variant (V) Of Lhsupporting
confidence: 51%
“…The hybridization assay may prove clinically useful in the differential diagnostics of delayed puberty. Raivio et al (1996) found that the V-LHb allele was associated with slow tempo of pubertal progression in boys, although the time of onset of puberty was not affected. In addition, pubertal boys homo-or heterozygous for the V-LH form were reported to have smaller testicular volumes, shorter stature and slower growth rates than boys with WT LH.…”
Section: Discussionmentioning
confidence: 94%
“…The association between V‐LH and reduced testes volume has been previously reported in a small study (49 boys) on pubertal onset and progression, where V‐LH carriers additionally exhibited slower pubertal progression and growth rate (Raivio et al ., 1996). Another study reported increased prevalence of V‐LH among cryptorchid boys born with gestational age > 40 weeks and suggested that the lower hormonal efficacy of V‐LH predisposes for improper testicular descent in late pregnancy (Kaleva et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Case–control association studies in male patients have suggested V‐LH as a risk factor for cryptorchidism (Kaleva et al ., 2005) and testicular cancer (Elkins et al ., 2003). A small‐scale study ( n  = 49) investigating the onset and progression of puberty in healthy boys reported slower progression of puberty and lower testes volume in V‐LH carriers (Raivio et al ., 1996). In a European cohort of middle‐aged and elderly men (EMAS study: n  = 2748 men, eight European countries), V‐LH was associated with reduced levels of serum LH (Huhtaniemi et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%